ADOPTION OF E - MEDICAL RECORDS ON PATIENT EXPERIENCES IN INDONESIAN PRIVATE HOSPITALS - Patricia Rani Rumondang; Felina C. Young; Imelda Imelda (CV. Fahr Publishing, 2026)
This study examines the adoption of Electronic Medical Records (EMR) and its impact on patient experience in Indonesian private hospitals, focusing on the mediating role of health service quality and patient safety. Based on the Information System Success Model (ISSM) and the Donabedian Outcome Process Structure framework, this study uses a quantitative survey design involving inpatients from two private hospitals in Central Java, Indonesia. Data were collected using a structured questionnaire compiled from validated measurement scales and analyzed through Partial Least Squares Structural Equation Modeling (PLS SEM). EMR adoption is measured through indicators of timeliness, accessibility, completeness, accuracy, and clinical decision-making support. Healthcare quality is measured by the SERVQUAL dimension, patient safety based on the International Patient Safety Goals (IPSG) and KARS standards, and patient experience using the Picker Institute's multidimensional framework. The results showed that the adoption of EMR significantly improved the quality of healthcare services (β = 0.756, p < 0.001) and patient safety (β = 0.725, p < 0.001), while directly improving the patient experience (β = 0.224, p < 0.001). Patient safety positively mediated the relationship between EMR adoption and patient experience (β = 0.282, p = 0.002), while quality of service showed a negative mediating effect (β = −0.248, p = 0.006) indicating a possible challenge of the workflow or adaptation process. The study concludes that EMR adoption plays a role as a strategic enabler that connects safety, quality, and patient experience. Effective governance, staff competence, and user-centric system design are critical to optimizing digital transformation and strengthening patient-centered healthcare in Indonesia's private hospitals.